2015
DOI: 10.1186/s12936-015-0756-6
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perception and satisfaction on quality of laboratory malaria diagnostic service in Amhara Regional State, North West Ethiopia

Abstract: BackgroundThe most effective strategies in the fight against malaria are to correctly diagnose and timely treat the illness. A diagnosis based on clinical symptoms alone is subjected to misuse of anti-malarial drugs, increased costs to the health services, patient dissatisfaction and also contributes to an increase in non-malaria morbidity and mortality. Among others, inappropriate perception and inadequate satisfaction of patients are significant challenges reported to affect the quality of laboratory malaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 10 publications
5
8
0
Order By: Relevance
“…However, socio-demographical features which are common in all the studies directly affect the patient satisfaction state (Hekkert, Cihangir, Kleefstra, & Berg, 2009;Bogale, Kassa, & Ali, 2015;Quintana, et al, 2006;Ercan, Idız, & Kan, 2004) as we have found in our study too.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…However, socio-demographical features which are common in all the studies directly affect the patient satisfaction state (Hekkert, Cihangir, Kleefstra, & Berg, 2009;Bogale, Kassa, & Ali, 2015;Quintana, et al, 2006;Ercan, Idız, & Kan, 2004) as we have found in our study too.…”
Section: Discussionsupporting
confidence: 70%
“…= 3,54) for both "discharge" and "post treatment care". Bogale et al (2015) have measured the patient satisfaction in different dimensions. According to this, the satisfaction rates were resulted as 84% for "punctuality of workers during working hours", 80% "ease of service access", 80% for "respectability of healthcare professionals" and 79% for "encouragement for acquisition of knowledge".…”
Section: Literature Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The sum total for all response-options produced a summative Likert score for that question. The summative Likert score was then divided by the total number of respondents to that question to produce an Agreement Score (weighted average ranging from "1" meaning that respondents strongly agree to that question down to "0" meaning that the respondents strongly disagree to that question) [8] [9] [10]. The scoring system was reversed for negative questions.…”
Section: Discussionmentioning
confidence: 99%